The age of Netflix : critical essays on streaming media, digital delivery and instant access - Barker, Cory, 1988-; Wiatrowski, Myc (Jefferson, North Carolina : McFarland & Company, Inc., Publishers, 2017)
"In 2016, Netflix expanded its online streaming video service to 130 new countries, adding more than 12 million subscribers in nine months and bringing its total to 87 million. In this collection of new essays, contributors explore how Netflix has become a cultural institution and transformed the way we consume popular media"--
Introduction (Cory Barker and Myc Wiatrowski); Part One: Netflix as Disruptor and as Cultural Institution; From Primetime to Anytime Streaming Video, Temporality and the Future of Communal Television (Justin Grandinetti); Terms of Excess: Binge-Viewing as Epic-Viewing in the Netflix Era (Djoymi Baker) ; Streaming Culture, the Centrifugal Development of the Internet and Our Precarious Digital Future (Joseph Donica); Part Two: Netflix as Producer and as Distributor Doing Time: Queer Temporalities and Orange is the New Black (Maria San Filippo)Netflix and Innovation in Arrested Development's Narrative Construction (Maíra Bianchini and Maria Carmem Jacob de Souza); Circulating The Square: Digital Distribution as (Potential) Activism (James N. Gilmore); Part Three: Netflix as Narrowcaster and as Global Player; Binge-Watching in Practice: The Rituals, Motives and Feelings of Streaming Video Viewers (Emil Steiner); Narrowcasting, Millennials and the Personalization of Genre in Digital Media (Alison N. Novak) From Interactive Digital Television to Internet "Instant" Television: Netflix, Shifts in Power and Emerging Audience Practices from an Evolutionary Perspective (Vivi Theodoropoulou) Digital Delivery in Mexico: A Global Newcomer Stirs the Local Giants (Elia Margarita Cornelio-Marí).
Includes bibliographical references and index.
Online resource; title from PDF title page (EBSCO, viewed August 31, 2017).
eBooks on EBSCOhost
Keywords: Netflix (Firm); Netflix (Firm); Streaming video -- Social aspects; Streaming technology (Telecommunications) -- Social aspects; Mass media -- Social aspects; Vidéo en continu -- Aspect social; En continu (Télécommunications) -- Aspect social; Médias -- Aspect social; BUSINESS & ECONOMICS -- Industries -- Media & Communications; TECHNOLOGY & ENGINEERING -- Telecommunications; Mass media -- Social aspects